Peningkatan Rendemen dan Kualitas Virgin Coconut Oil (VCO) dengan Metode Fermentasi sebagai Upaya Efisiensi Pemanfaatan Komoditas Lokal Kalimantan Utara - Nurjannah, Nurjannah; Santoso, Dwi; Egra, Saat; Nurhafizah, Nurhafizah (Universitas Respati Indonesia, 2026)
The processing of coconuts into Virgin Coconut Oil (VCO) is an alternative coconut processing method with strong potential for development in North Kalimantan, considering the region’s favorable environmental conditions for coconut cultivation. Over the past three years, coconut production in North Kalimantan has continued to decline, even though the number of productive coconut plantations remains relatively high. This decline in production is primarily attributed to the low bargaining price of fresh coconuts in the region. Therefore, alternative coconut processing strategies are needed to restore the economic value and purchasing power of coconuts. One promising coconut processing product is VCO. VCO can be produced using a fermentation technique that utilizes microorganisms present in yeast. In the fermentation-based VCO processing method, coconut milk is first allowed to settle until it forms a cream layer. The cream is then inoculated with yeast containing microorganisms such as Saccharomyces cerevisiae and Rhizopus oligosporus. These microorganisms produce protease and lipase enzymes, which hydrolyze the oil in the coconut cream with a high moisture content. Differences in processing techniques can influence the oil yield obtained. The use of yeast in VCO fermentation, combined with longer fermentation times, is expected to increase the yield. In this study, VCO was produced using yeast as a fermentation starter, and the resulting VCO was subsequently analyzed for quality. The experiment employed a Randomized Block Design (RBD). Two factors were observed: the type of yeast, consisting of V (without yeast), VR (bread yeast), and VT (tape yeast), and fermentation time, consisting of T1 (36 hours), T2 (48 hours), and T3 (60 hours). Each treatment was replicated three times, resulting in 9 treatments × 3 replications = 27 experimental units. The produced VCO was then analyzed for yield, as well as its physical and chemical properties. The results showed that treatment VRT3 (bread yeast with a fermentation time of 60 hours) produced the highest yield, reaching 25%. Furthermore, longer fermentation times resulted in higher VCO yields